SENGKETA LAUT CINA SELATAN PASCA PUTUSAN PERMANENT COURT OF ARBITRATION TAHUN 2016 PERSPEKTIF HUKUM INTERNASIONAL - NURSYAMSIAH NURSYAMSIAH (JOURNAL OF LAW AND NATION, 2025)
China's unilateral claims in the South China Sea have triggered disputes due to overlapping claims by several countries in the Southeast Asia region and China. This study aims to analyze the South China Sea disputes post the Permanent Court of Arbitration (PCA) ruling in 2016 from an international law perspective. The method used is a normative juridical approach with literature study and analysis of official documents and foreign policies of each country post-PCA ruling. The results show that although the PCA ruling is final and binding under UNCLOS 1982, its implementation on the ground still faces political and diplomatic obstacles. China's non- compliance with the ruling presents a significant challenge in enforcing international law when dealing with major countries. However, the ruling remains an important precedent in the peaceful resolution of maritime disputes based on international law. The success of international law in the South China Sea disputes does not only depend on the legal decision itself but also on the political will of countries to comply with and respect the applicable law. A more assertive, participatory, and consistent multilateral approach is needed for the supremacy of international law to be effectively upheld in the resolution of future maritime conflicts